2009
DOI: 10.1055/s-0029-1218606
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of (-)-Circumdatin H, a Novel Mitochondrial NADH Oxidase Inhibitor

Abstract: An efficient and highly convergent synthesis of the mitochondrial NADH oxidase inhibitor (-)-circumdatin H is described. The strategy employs the intramolecular Eguchi aza-Wittig protocol as a key step to install the crucial central core BC ring system, leading to the first total synthesis of the target molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Surprisingly, the effectiveness of Weinreb amides (AcN(OMe)Me, i PrCON(OMe)Me) in the acylation of 4a was very low and the desired products 5a,b were formed in trace amounts (Table 1, entries 13,16). Besides products 2 or 5 and mentioned above N-acetyl carbamate 3 (as an effect of the reaction of 1a with Ac2O, Table 1, entry 3), from the post reaction mixture some amounts of starting carbamates 1 or 4 (10-50%), ketoamide 6 (8%), N-Boc 2-naphthylamine 7 (5-60%) and naphtho[2,1-d] [1,3]oxazin-3-one 8 (5-10%) were also isolated (confirmed by 1 H, 13 C NMR, HRMS, Table 1, entries 11,[13][14][15]. The formation of ketoamide 6, appears to result from the C-acylation of lithiated N-(naphthalen-2-yl)acetamide 9 by Ac2O, followed by quenching with methanol.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Surprisingly, the effectiveness of Weinreb amides (AcN(OMe)Me, i PrCON(OMe)Me) in the acylation of 4a was very low and the desired products 5a,b were formed in trace amounts (Table 1, entries 13,16). Besides products 2 or 5 and mentioned above N-acetyl carbamate 3 (as an effect of the reaction of 1a with Ac2O, Table 1, entry 3), from the post reaction mixture some amounts of starting carbamates 1 or 4 (10-50%), ketoamide 6 (8%), N-Boc 2-naphthylamine 7 (5-60%) and naphtho[2,1-d] [1,3]oxazin-3-one 8 (5-10%) were also isolated (confirmed by 1 H, 13 C NMR, HRMS, Table 1, entries 11,[13][14][15]. The formation of ketoamide 6, appears to result from the C-acylation of lithiated N-(naphthalen-2-yl)acetamide 9 by Ac2O, followed by quenching with methanol.…”
Section: Resultsmentioning
confidence: 88%
“…The quinazoline or quinazolinone skeleton is a building block of various alkaloids 1,2 with diverse biological activities [3][4][5] like for example vasicine and vasicinone (active compounds of Justicia athatoda), [6][7][8] asperlicins A-E (fungal metabolite components of Aspergillus alliaceus) 9,10 or circumdatin H (from the fungus Aspergillus ochraceus). 11 It has been shown that e.g. asperlicin and its analogues can act as antagonists of neurotransmitter cholecystokinin (CCK).…”
Section: Introductionmentioning
confidence: 99%
“…44 The required tripeptide 136 was prepared from isatoic 45 Intermediate 138 was prepared from anthranilic acid derivatives in a convergent manner which on the intramolecular aza-Wittig reaction of azide with imide carbonyl provided (−)-circumdatin H (139) in 4 steps with 48% overall yield. 44 The required tripeptide 136 was prepared from isatoic 45 Intermediate 138 was prepared from anthranilic acid derivatives in a convergent manner which on the intramolecular aza-Wittig reaction of azide with imide carbonyl provided (−)-circumdatin H (139) in 4 steps with 48% overall yield.…”
Section: Quinazolinobenzodiazepine Alkaloidsmentioning
confidence: 99%
“…44 The required tripeptide 136 was prepared from isatoic Bose et al reported the first total synthesis of (−)-circumdatin H (139), a novel mitochondrial NADH oxidase inhibitor (Scheme 24). 45 Intermediate 138 was prepared from anthranilic acid derivatives in a convergent manner which on the intramolecular aza-Wittig reaction of azide with imide carbonyl provided (−)-circumdatin H (139) in 4 steps with 48% overall yield. The intramolecular aza-Wittig reaction was the key step of synthesis.…”
Section: Quinazolinobenzodiazepine Alkaloidsmentioning
confidence: 99%
“…In the development of strategies for the preparation of heterocycles, the aza‐Wittig reaction has proved to be a powerful tool for the synthesis of five‐to‐eight‐membered nitrogen heterocycles [21–30] including natural products [31–36]. The iminophosphorane of heterocyclic and heteroaromatic β‐enamino esters have proved to be very versatile intermediates for the construction of manifold hetero‐condensed system.…”
Section: Introductionmentioning
confidence: 99%